2015
DOI: 10.2494/photopolymer.28.131
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carbon Films Prepared from Polybenzoxazine Films

Abstract: Two types of polybenzoxazine films, PBa and PPd, that were prepared by the thermal cure of benzoxazines, Ba and Pd, were carbonized at temperature-controlled condition, and the effect of the chemical structure of the polybenzoxazines on carbonization was examined by comparing with the carbonization behavior of polyimide film. X-ray diffraction and X-ray photoelectron spectra measurements showed that the carbon films prepared by heat treatment of rigid polybenzoxazine, PPd, at 900 °C and 1000 °C were the most g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The XRD results demonstrated that graphitization increased with higher carbonization temperatures, as noted by the higher (002) diffraction peaks [58]. XPS analysis was able to provide similar results, and also demonstrated that despite PI being known as a good graphite precursor, the PH-ddm yielded more significant graphitization, thus further demonstrating the thermal stability of benzoxazine films and that graphitization is possible [58]. GDC curves can be used to determine further capacitive and current properties.…”
Section: Electrochemical Propertiesmentioning
confidence: 74%
See 2 more Smart Citations
“…The XRD results demonstrated that graphitization increased with higher carbonization temperatures, as noted by the higher (002) diffraction peaks [58]. XPS analysis was able to provide similar results, and also demonstrated that despite PI being known as a good graphite precursor, the PH-ddm yielded more significant graphitization, thus further demonstrating the thermal stability of benzoxazine films and that graphitization is possible [58]. GDC curves can be used to determine further capacitive and current properties.…”
Section: Electrochemical Propertiesmentioning
confidence: 74%
“…Benzoxazines can also be prepared as films, as seen in films made from easily carbonized polyimides (PI) or oth al. prepared carbon films derived from either bisphenol A or phenol/diaminodiphenylmethane (abbreviated as PHpolyimide made from pyromellitic dianhydride (PD) and characterized by X-ray diffraction (XRD) and X-ray photoel XRD results demonstrated that graphitization increased w peratures, as noted by the higher (002) diffraction peaks provide similar results, and also demonstrated that desp graphite precursor, the PH-ddm yielded more significan demonstrating the thermal stability of benzoxazine films a ble [58].…”
Section: Carbon Filmsmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, they were used as cross-linking agents for the poly­(2,5-benzimidazole)-based electrolyte membrane in order to prevent its dissolving in phosphoric acid or as the mold antisticking layer for nanoimprinting lithography. , Generally, benzoxazine monomers are powders with melting temperatures higher than 90 °C, which is the main disadvantage of their use in the preparation of PBz-based materials, as the solvent is often required for the film preparation . The use of toxic solvents (such as chloroform, tetrahydrofuran, and dimethylformamide ) causes the main drawback to the benefit of the simplicity and flexibility of the PBz synthesis.…”
Section: Introductionmentioning
confidence: 99%